2008
DOI: 10.1016/j.abb.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage tensile integrity: Modulation by matrix depletion is maturation-dependent

Abstract: Articular cartilage function depends on the molecular composition and structure of its extracellular matrix (ECM). The collagen network (CN) provides cartilage with tensile integrity, but must also remodel during growth. Such remodeling may depend on matrix molecules interacting with the CN to modulate the tensile behavior of cartilage. The objective of this study was to determine the effects of increasingly selective matrix depletion on tensile properties of immature and mature articular cartilage, and thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…The physical, chemical and biological regulation of the cellular microenvironment is essential to maintain the spatial and temporal behavior of chondrocytes. Cartilage is avascular and aneural; thus, chondrocytes require nourishment by the slow diffusion of synovial fluid (12). Although the traditional two-dimensional (2D) cell culturing technique was typically adopted to explore the optimal expansion environment for chondrocytes in vitro, it remains controversial whether chondrocytes grown in vitro are morphologically identical to those present in vivo (13).…”
Section: Introductionmentioning
confidence: 99%
“…The physical, chemical and biological regulation of the cellular microenvironment is essential to maintain the spatial and temporal behavior of chondrocytes. Cartilage is avascular and aneural; thus, chondrocytes require nourishment by the slow diffusion of synovial fluid (12). Although the traditional two-dimensional (2D) cell culturing technique was typically adopted to explore the optimal expansion environment for chondrocytes in vitro, it remains controversial whether chondrocytes grown in vitro are morphologically identical to those present in vivo (13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with cultured chondrocytes encapsulated in agarose have shown higher compressive stress with increasing sGAG content with time in culture. 30,50 Depletion of PG in immature cartilage has been shown to increase tensile strength 21 and may alter biomechanical properties in tissue-engineered constructs as well. 22 Studies of in vitro collagen fibril assembly have shown that the presence of PG, such as CS or AGC, alters size and rate of fibril formation and the mechanical properties of the resulting collagen-PG material as compared to collagen alone.…”
Section: Figmentioning
confidence: 99%
“…The samples were incubated with 1 mM 4-(2-aminoethyl) benzenesulfonyl fluoride hydrochloride for 2 h at 378C to inhibit proteinase K and assayed using HA test kit (Corgenix). 21 HA was analyzed in PBS pooled from day 1 to 3, because the amount released was small in comparison to sGAG release as determined from a pilot study (Supplemental Material, available online at www.liebertonline.com/ten).…”
Section: Biochemical Analysis Of Released and Retained Pg Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another method, selective enzymatic degradation of PG in cartilage and engineered constructs resulted in increased COL concentration, COL:PG ratio, and tensile stiffness of the tissue. [14][15][16] These approaches highlight the importance of the content of and balance between COL and PG in the mechanical function of tissue-engineered constructs. However, direct mechanical compaction to increase ECM concentration and mechanical function has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%